(untitled) (Journal of Academic Research, 2025)
copper(II) complex, [Cu(bpy)₂]Cl₂. The complex was synthesized using a modified procedure based on the reaction of CuCl₂·2H₂O with 2,2’-bipyridine. Structural and physicochemical properties were elucidated through X-ray diffraction (XRD), scanning electron microscopy (SEM), atomic force microscopy (AFM), dynamic light scattering (DLS), and zeta potential analysis. XRD revealed a highly crystalline structure, while SEM and AFM showed a layered morphology with nanoscale features. DLS indicated a mean hydrodynamic diameter of 45 nm, and zeta potential measurements suggested moderate colloidal stability with a surface charge of -25 mV. The complex exhibited significant antimicrobial activity against Escherichia coli, demonstrating an inhibition zone of 18 ± 1 mm, comparable to the gentamicin control (22 ± 1 mm). This activity is attributed to potential mechanisms including reactive oxygen species generation, DNA interaction, protein denaturation, and membrane disruption. The findings suggest that this Cu(II) complex holds promise as a novel antimicrobial agent, warranting further investigation into its broader applicability and mechanism of action.